Controlling the Casimir force / Khoo Yee Yang - Khoo, Yee Yang (2013)
This research is devoted to a detailed study of the Casimir effect, and means to control it. The study is subdivided into two objectives. First, the origin of Casimir force and its physical significance is explored. Several different approaches and interpretations of the Casimir force is detailed and discussed. In particular, the Casimir force was derived from the vacuum field approach, the vacuum radiation approach and the source theory approach. It is concluded that the Casimir force may be equally interpreted as the manifestation of vacuum field, or the source field. Second, the possible means of controlling the Casimir force is detailed. By analysing the Lifshitz formula, we have discussed the material dependence of Casimir force. Metamaterial, with its unique ability to behave electrically and magnetically at different frequency range is shown to exhibit stable and unstable equilibrium in its Casimir force. The idea of controlling the Casimir force via optical means is then introduced theoretically. A system consisting of a metamaterial placed parallel to a Kerr material is shown to exhibit tunable Casimir force by varying the impinging laser intensity. As a result, it is shown that the Casimir force may be controlled both optically and by varying the materials involved. This finding is important, as it provides new possibilities of integrating optical devices into nanoelectrome chanical systems.